Low cycle fatigue behavior of additively manufactured Ti-6Al-4V under non-proportional and proportional loading - Stefano Bressan; Fumio Ogawa; Takamoto Itoh; Filippo Berto (Fracture and Structural Integrity)
Experimental tests were conducted on additive manufactured Ti-6Al-4V titanium alloy to investigate the mechanical and crack properties under multiaxial cyclic loading. Selective Laser Sintering technique (SLS) was employed to fabricate four types of cylindrical hollow specimens. The typology of each specimen is defined by the orientation of the layers and by the application of a stress-relieving heat treatment after the production process. Stress-strain cyclic curves of the materials were obtained to investigate the material cyclic plastic behavior, that resulted independent of specimen variety. Strain-controlled multiaxial low cycle fatigue tests under proportional and non-proportional loading paths were carried out on the specimens. Not heat-treated specimens exhibited a higher low cycle fatigue resistance both for proportional and non-proportional loading. Drastic initial softening was detected in the majority of the tests. Additional hardening was detected in part of non-proportional tests, which is atypical for this alloy. The mutual influence of applied load and microstructural characteristics on fatigue life are finally discussed.